2012
DOI: 10.1002/sce.21007
|View full text |Cite
|
Sign up to set email alerts
|

Stability and volatility of STEM career interest in high school: A gender study

Abstract: This retrospective cohort study characterizes how interest in science, technology, engineering, mathematics (STEM) careers changes during high school for more than 6,000 students in a representative national sample of 34 two‐ and four‐year colleges taking mandatory college English courses. Overall, large gender differences in career plans were found, with males showing far more interest particularly in engineering, whereas females were more attracted to careers in health and medicine during their high school y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
408
9
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(466 citation statements)
references
References 27 publications
32
408
9
17
Order By: Relevance
“…The results show that students' individual interest in physics over the course investigated in the present study (up to six months between T1 and T2) remains relatively stable (see high auto-regression between T1 and T2 in within-part of the model in Figure 3). This is in line with theoretical considerations on the stability or changeability of individuals' belief systems (e.g., Rokeach, 1985) as well as previous studies showing interest as a relatively stable preference in students (e.g., Hofstein & Welch, 1984;K€ oller et al, 2001;Sadler, Sonnert, Hazari, & Tai, 2012;Tracey, Robbins, & Hofsess, 2005). However, the results also reveal that students' interest at T2 is predicted by the teacher or more specifically the teachers' motivation and enthusiastic teaching behaviors (see between-part of the model in Figure 4).…”
Section: Interest and Its Relation To Achievementsupporting
confidence: 90%
“…The results show that students' individual interest in physics over the course investigated in the present study (up to six months between T1 and T2) remains relatively stable (see high auto-regression between T1 and T2 in within-part of the model in Figure 3). This is in line with theoretical considerations on the stability or changeability of individuals' belief systems (e.g., Rokeach, 1985) as well as previous studies showing interest as a relatively stable preference in students (e.g., Hofstein & Welch, 1984;K€ oller et al, 2001;Sadler, Sonnert, Hazari, & Tai, 2012;Tracey, Robbins, & Hofsess, 2005). However, the results also reveal that students' interest at T2 is predicted by the teacher or more specifically the teachers' motivation and enthusiastic teaching behaviors (see between-part of the model in Figure 4).…”
Section: Interest and Its Relation To Achievementsupporting
confidence: 90%
“…College students reported that their decision to consider a STEM major was made during high school rather than at graduation; student interest was found to be the important consideration, followed by parental influence, earning potential, and teacher influence, respectively [4]. These findings strongly suggest introduction to these fields in a memorable manner during high school is vital if students are to be encouraged to pursue STEM fields, especially within engineering [5].…”
Section: Introductionmentioning
confidence: 94%
“…Öz-düzenleyici öğrenme, öğrencilerin kendi öğrenme hedeflerini belirledikleri, Çünkü öğrencilerin fizik ve biyoloji dersi için erken yıllarda geliştirdikleri kaynak yönetimi stratejileri daha sonraki yıllarda ve üniversitede fizik ve biyoloji öğrenme yöntemlerini etkilemektedir (Sadler, Sonnert, Hazari, & Tai, 2012).…”
Section: Sonuç Ve Tartışmaunclassified